Radiation Coordinates of Florides - McCrea - Synge - López-Bonilla, J.; López-Vázquez, R.; Pérez-Teruel, G. R. (Journal of the Institute of Engineering, 2016)
In this work we construct the element of volume vector dσ of a r surface of constant retarded distance around the trajectory of a charged particle with arbitrary motion in a Riemannian space. This constitutes a generalization of the method pioneered by Synge [1] in special relativity. The technique r employed is suggested by the ‘radiation coordinates’ y introduced by Florides-McCrea-Synge [2, 3] in the study of gravitational radiation. Journal of the Institute of Engineering, 2015, 11(1): 151-157